Research and development on coatings and paints for geothermal environments: a review - Fanicchia, Francesco; Karlsdóttir, Sigrún N. (Wiley, 2023)
Geothermal power plants are complex systems, where the interplay between different metallic components transforms the enthalpy of hot brine in the form of electricity or usable heated water. The naturally occurring variety in brine chemistry, linked to the presence of specific key species, and its thermo-physical properties, leads to the development of different power plant configurations. Key species and power plant configuration in turn determine the extent of damage experienced by each component in the power plant: erosion, corrosion, and/or scaling, often acting combined. Paints and coatings, compared to changing the component alloy, have represented a preferred solution to mitigate these issues due to advantages in terms of costs and repairability. This is reflected in the large number of publications on research and development in this area within the past ≈50 years, with even an increasing trend in the past 10–20 years, indicating the strong interest to develop this clean and sustainable energy source. Therefore, in this work, the first of its kind after 1980, an in-depth review of all published work on research performed on paints and coatings for geothermal applications, subdivided by the material system, is provided.